INTERNALIZING PANCASILA THROUGH POP CULTURE AND YOUTH COMMUNITY - Ranny Rastati (Jurnal Masyarakat dan Budaya, 2022)
This paper aims to understand how to internalize the values of Pancasila among the younger generation, which are Millennials and Generation Z, in Indonesia. The method used is a qualitative approach with in-depth interviews, focus group discussions (FGD), and literature study for data collection. The study was conducted from May 2021 to January 2022. The results showed that Pancasila needs to be internalized by the younger generation to maintain the spirit of Bhinneka Tunggal Ika (unity in diversity) from generation to generation. Promoting Pancasila values can be done through pop culture products such as film, animation, and music can also be a medium to internalize the values of Pancasila. In addition, youth communities with offline and online programs such as Pancasila schools, positive content on social media such as vlogs, memes, short videos, and humanitarian donations. The non-indoctrinated process makes the values of Pancasila can be understood by the young generation and implemented in a daily manner, not just an ideology.